Can CD44+/CD24- Tumor Cells Be Used to Determine the Extent of Breast Cancer Invasion Following Neoadjuvant Chemotherapy? - Wu, Hong (Korean Breast Cancer Society, 2011)
PURPOSE: To investigate the distribution of CD44(+)/CD24(-) cells in breast cancers in relation to tumor size before and after the administration of neoadjuvant chemotherapy. METHODS: CD44(+)/CD24(-) tumor cells obtained from breast cancer specimens were characterized in vivo and in vitro using tumor formation assays and mammosphere generation assays, respectively. The distribution of CD44+/CD24- tumor cells in 78 breast cancer specimens following administration of neoadjuvant chemotherapy was also evaluated using immunofluorescence assays, and this distribution was compared with the extent of tumor invasion predicted by Response Evaluation Criteria in Solid Tumours (RECIST). RESULTS: In 27/78 cases, complete remission (CR) was identified using RECIST. However, 18 of these CR cases were associated with a scattered distribution of tumor stem cells in the outline of the original tumor prior to neoadjuvant chemotherapy. After neoadjuvant chemotherapy, 24 cases involved cancer cells that were confined to the tumor outline, and 21 cases had tumor cells or tumor stem cells overlapping the tumor outline. In addition, there were 6 patients who were insensitive to chemotherapy, and in these cases, both cancer cells and stem cells were detected outside the contours of the tumor volume imaged prior to chemotherapy. CONCLUSION: CD44+/CD24- tumor cells may be an additional parameter to evaluate when determining the extent of breast cancer invasion.